(untitled) (Economics and region, 2021)
There are various sources of sales of organic products, their advantages and disadvantages are considered in the article. The distribution of different sales channels of such products is developed European countries is given. The main attention is paid to the motivational factors of the purchase of organic products at different points of sale and the implementation of specific marketing strategies for the agri-food system in the market of organic products is proposed. It is the development of sales of organic products among producers in the regions and effective organization of exchange and trade, their optimal territorial organization are the most important factors in stabilizing organic production and an important prerequisite for saturation of the food market. The methodological basis of the study is the dialectical method of cognition, modern concepts of organization and management of sales channels of organic products, general scientific techniques and methods, in particular: abstract-logical; historical and economic; statistical and economic; system-structural. The system approach is used in the work, which consists in a complex research of sales channels of organic products.